The Media question card asisten take and give learning model on student civil knowledge competence class IV SD Negeri 136539 - Riska, Devi (Journal of General Education Science, 2023)
The background of this research is students whose competency skills in Civics knowledge are still lacking and are still limited so that students have not been able to understand Civics knowledge. The purpose of this study was to determine the effect of the take and give learning model assisted by question card media on Civics knowledge competence. The population in this study were all 25 students of grade IV. The sampling technique in this study used total sampling. The sample in this study amounted to 25 students. This research instrument uses a test sheet. Data analysis techniques in this study used validity tests, reliability tests, and hypothesis testing. The results of this study indicate that the Take and Give learning model has an effect on Civics knowledge competencies, <0.05, then Ha is accepted and H0 is rejected. This means that there is an influence of the take and give learning model assisted by question card media on the competence of Civics knowledge of Grade IV students at SD N 136539 Tanjungbalai City. The results of data analysis obtained an average (mean) after being given treatment using the take and give learning model, namely 82.4. Whereas before being given the treatment of the Take and Give learning model the average (mean) was 58. So that students who received treatment using the Take and Give learning model had a higher average when compared to without using the Take and Give learning model